Heterogeneous Effects of Unconventional Monetary Policy on the Bond Yields across the Euro Area - (:unkn) unknown (WILEY, 2021)
This paper investigates the impact of the European Central Bank's unconventional monetary policies (UMP) between 2008 and 2019 on European government bond yields. It adopts a novel econometric approach that combines a data-rich factor analysis and Vector autoregression (VAR) with heteroskedastic-based identification. The results identify a significant and substantial impact for all countries and maturities, but stronger and persistent impact for the periphery. When we decompose the impact into separate components, we find that UMP decreases the market component for all countries. It decreases the risk-mutualization component for the periphery permanently at the cost of a small increase for the core countries, which provides evidence for risk-mutualization in the EMU.
Keywords: cross-country difference; ECB; EMU; risk-mutualization; sovereign bond yields; unconventional monetary policya; IMPACT; PURCHASES; CRISIS; NUMBER